Mempelajari Pengaruh Komposisi Bioarang Berbahan Baku Batubara dan Pelepah Kelapa Sawit terhadap Karakteristik Briket - Ipang Setiawan (Jurnal Agricultural Biosystem Engineering, 2022)
Biomass from oil palm fronds in Central Lampung has not been fully utilized, so there is a need for alternatives to the processing of aggregations into more useful materials. One of the uses of oil palm fronds is to make it an alternative fuel, namely bioarang briquettes. The aim of this study is to determine the effect of the oil palm fronds and the size of the oil palm fronds on the characteristics of the bioarang briquettes. The raw materials used are: palm fronds, carbon and tapioca adhesives. The study used a fully randomized design (CRD) factorial with one factor. Namely, the size of the oil palm fronds that escaped the sieve (M) with one treatment, namely 20 mesh. As a result, 5 treatments with 5 replications were obtained so that 25 experimental units were obtained. Subsequently, the data were obtained in the LSD test. Keywords:  Briquettes, Carbon, Palm Fronds, Tapioca Flour.